The influence mechanism of parental emotional companionship on children’s second language acquisition - Cheng, Xiaoxia; Zhou, Shike (Frontiers in Psychology, 2023)
In this study, path analysis was used to explore the mechanism of parental emotional companionship on children's second language acquisition. The results show that learning confidence, internal learning motivation and further study motivation mediate the relationship between parental emotional companionship and children's second language acquisition.Learning confidence positively influences internal learning motivation and further study motivation and plays a chain mediating role in this relationship. The indirect effect of learning motivation in the middle school group is the shadowing effect. These conclusions can provide inspiration for parents to assist their children in second language acquisition and improve the quality of family education.